Family impact on capital structure: does financial crisis matter? - Lisboa, Inês (2018)
This study analyses whether family control impacts the firm’s capital structure and if results are influenced by financial turbulences. Using a sample of Portuguese listed firms during fourteen years, results show that family and-non family firms have different debt levels in periods of expansion. Moreover, the higher concentration of family ownership leads to reduction in the firm’s leverage, especially in recession periods. These results confirm the behavioural-agency theory: the family looks to socio-emotional wealth but assuring the firm presence for future generations.